Growth Abnormalities in Children with Chronic Hepatitis B or C - P. Gerner; Andre Hörning; S. Kathemann; K. Willuweit; S. Wirth (Advances in Virology)
Background. It has been suggested that chronic hepatitis B infection leads to growth impairment, but data are inconsistent and underlying factors are not defined. Methods. Children and adolescents with chronic hepatitis B (HBV) or C (HCV) were retrospectively evaluated for growth, weight, antiviral treatment, biochemical signs of liver inflammation, route of infection, and HBV DNA, respectively. Results. In all, 135 children (mean age 6.1 years, 81 male, 54 female) with HBV (n=78) or HCV (n=57) were studied. Route of infection was vertical in 50%, parenteral in 11%, and unknown in 39%. ALT levels were above 1.5 times above normal in 30% while 70% had normal/near normal transaminases. 80% were Caucasian, 14% Asian, 1% black, and 4% unknown. Mean baseline height measured in SDS was significantly lower in the study population than in noninfected children (boys −1.2, girls −0.4, P<0.01). 28 children were below 2 standard deviations of the norm while 5 were above 2 standard deviations. SDS measures in relation to individual factors were as follows: elevated ALT: boys −1.4, females −0.5 (P<0.01), ALT normal/near normal: boys +0.4, females +0.6; parenteral transmission: boys −3.3, girls −0.9 (P<0.01), vertical transmission: boys −0.2, females −0.2. Antiviral treatment itself or HBV-DNA load did not reach statistically significant differences. Conclusions. Chronic HBV or HCV may lead to compromised growth which is mostly influenced by liver inflammation. Our data may argue for early antiviral treatment in children with significant ALT elevation.